'It may also be our own fault to think so, to limit them before even trying': Assuming Learner Limitations during Materials Design in English Language Teacher Education. Issue 4 (27th January 2022) - Carabantes, Luis; Paran, Amos
Abstract : Whilst the scholarship into language teaching materials and into language teacher education has gained considerable vitality since the mid‐90s, the intersection of both fields has remained largely disconnected from one another from a research perspective. Bridging this gap, this study explores how a group of Chilean preservice teachers of English learn to design language teaching materials towards the end of their teacher education course. Drawing on the sociocultural framework of Activity Theory and using qualitative data from preservice teachers, teacher educators and mentoring teachers, it was possible to identify 'Assuming Learner Limitations' as one of the main rationales mediating the design of language teaching materials by the preservice teachers. The data also showed how this rationale emerged from the preservice teachers' disparaging beliefs about their learners, and how its development was promoted by the school mentors at the schools where they were doing their practicum, despite the teacher education course efforts to prevent its emergence. The study highlights the importance of addressing materials evaluation, adaptation and design in initial teacher education, and the need for conducting more research into the intersection of teacher education and materials development to both expand our knowledge of teaching materials as well as understand how student‐teachers relate to the tools of their future profession.